International business and multinational enterprises - Robock, Stefan H.; Simmonds, Kennth (Burr Ridge : Irwin, 1989)
Business
Keywords: International business enterprises; Foreign exchange; Multinational marketing management; Multinational financial management; global business strategy; Multinational operations management